Implementasi Extensive Reading Activity Dalam Pengajaran Mata Kuliah Reading Pada Mahasiswa IAIN Manado - Anis Komariah (Institut Agama Islam Negeri (IAIN) Samarinda, 2021)
The purpose of the research is to describe the implementation of Extensive Reading Activity in Reading Comprehension subjects for IAIN Manado students. The research used a qualitative descriptive method. The data were collected through field notes, observation, documentation, and interview. The subjects of this research were students of Tadris Bahasa Inggris IAIN Manado. The findings show that the lecturer had implemented the Extensive Reading Activity in the Reading subject. The implementation of the Extensive Reading Activity for Students of Tadris Bahasa Inggris IAIN Manado can be concluded that there are many advantages in reading skills: understanding vocabulary, structure, grammar, and finding ideas or general descriptions in a text. The Extensive Reading approach can increase students' knowledge and worldview, foster attitudes and motivation towards reading habits, so reading is a fun activity and improves their Reading Skills. However, the Extensive Reading approach cannot replace the Intensive Reading approach. Moreover, Extensive Reading Activity is an alternative way of teaching and learning Reading skills. Through this research, it is hoped that it can provide an overview of Extensive Reading Activity's implementation, especially in the Reading subject, to be used as a reference for further research.